Determination of warning level at Lang Son environmental radiation monitoring station - Nguyen , Van Khanh; Duong , Van Thang; Nguyen , Thi Oanh; Nguyen , Thi Thu Ha; Doan , Thuy Hau; Le , Thi Hoa; Cao , Duc Viet; Duong , Duc Thang (Nuclear Science and Technology, 2021)
In this study, a method to estimate the baseline of ambient dose equivalent rate (ADER) of the Lang Son radioactive monitoring station was presented. The warning level is calculated from the arithmetic mean and standard deviation of the terrestrial background value. The terrestrial background value estimated from the Radon peak removal algorithm is 39.85 nSv/h with a standard deviation of 7.58 nSv/h. For comparison, the soil samples around the monitoring equipment were collected and analyzed the activity concentration of nuclides 226Ra, 232Th, 40K. The terrestrial background value estimated from these values of activity concentration is of 41.10 ± 2.96 nSv/h. There is a good agreement between the results evaluating ADER from Radon peak removal algorithm and from the activity concentration of nuclides 226Ra, 232Th, 40K.